The Evolution Path and Impact Mechanism of the Vulnerability of Rural Human Settlements in China under the Background of Globalization - Liu, Fulong; Lin, Baogang; Meng, Kun (Problemy Ekorozwoju, 2024)
Development in the rural environment is a key pillar motivating international organizations’ functions and operations. The development in this area falls under the 2030 Agenda of Sustainable Development of the UN. Rural development and factors such as culture might be utilized to achieve such agenda and improve populations living in conditions. The current study was literature systemic reviewing the evolution path and the impact mechanism on the issue of rural human settlement. Results in the current study showed that natural ecosystems, socioeconomic systems, facilities, and service systems all follow one of seven general evolution paths. Terrain and ecology, climate change and catastrophe, the agricultural and rural economy, population increase, and other factors all contribute to disruption. Policy, technology, and the habits of individual households inform the development of action plans. Every evolutionary outcome has both fragile and hardy features. The government and individual families took measures to lower vulnerability and increase resilience by concentrating on the actual problem of the rural human settlements system. Further, the study observed that the effects of rural human settlements on rural development occur in a systematic way. These changes, most obviously seen in the form of new and improved rural human settlement projects, have the potential to affect many facets of the human settlement system as a whole, making it cleaner, more practical, more harmonic, and generally more pleasant places to live. These benefits will have a multiplicative impact on the health, wealth, and happiness of rural residents; the efficiency, modernity, and prosperity of rural businesses; and the quality of life in rural areas.